2016
DOI: 10.1038/srep23825
|View full text |Cite
|
Sign up to set email alerts
|

Sex reversal assessments reveal different vulnerability to endocrine disruption between deeply diverged anuran lineages

Abstract: Multiple anthropogenic stressors cause worldwide amphibian declines. Among several poorly investigated causes is global pollution of aquatic ecosystems with endocrine disrupting compounds (EDCs). These substances interfere with the endocrine system and can affect the sexual development of vertebrates including amphibians. We test the susceptibility to an environmentally relevant contraceptive, the artificial estrogen 17α-ethinylestradiol (EE2), simultaneously in three deeply divergent systematic anuran familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 68 publications
8
74
0
Order By: Relevance
“…Tamschick et al, 2016). BPA-treatments involved two non-model species, H. arborea and B. viridis, and the ecotoxicology model amphibian X. laevis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tamschick et al, 2016). BPA-treatments involved two non-model species, H. arborea and B. viridis, and the ecotoxicology model amphibian X. laevis.…”
Section: Discussionmentioning
confidence: 99%
“…DNAs were eluted in 200 ml AE buffer (Qiagen) and stored at À20 C. To establish genetic sex, species-specific polymerase chain reactions (PCRs) were conducted with subsequent gel electrophoresis and genotyping. Sexing of H. arborea and X. laevis was conducted as described (Tamschick et al, 2016), sexing of B. viridis involved markers C201, C223 (Tamschick et al, 2015), Cherp, DMRT1 and VLDLR (Gerchen et al, 2016). Only frogs and toads that completed metamorphosis were genetically sexed.…”
Section: Dna Extraction Pcrs and Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some EDCs with weak estrogenic activities, such as BPA and PCBs, were reported to cause significant intersexes in X. laevis (Kloas et al, 1999;Levy et al, 2004;Qin et al, 2003). Furthermore, estrogenic pharmaceuticals were demonstrated to result in complete male-to-female reversal in X. laevis; for instance, Tamschick et al (2016) reported that 50, 500, 5000 ng/L EE2 caused 31.3%, 76.5% and 100% phenotypic females in genetic males, respectively. The data have enough demonstrated high sensitivity of X. laevis gonadal differentiation to estrogenic EDCs.…”
Section: Introductionmentioning
confidence: 99%